The Role of Mitochondrial Dysfunction and ER Stress in TDP-43 and C9ORF72 ALS - Dafinca, Ruxandra; Barbagallo, Paola; Talbot, Kevin (Frontiers in Cellular Neuroscience, 2021)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease of the motor system with complex determinants, including genetic and non-genetic factors. Despite this heterogeneity, a key pathological signature is the mislocalization and aggregation of specific proteins in the cytoplasm, suggesting that convergent pathogenic mechanisms focusing on disturbances in proteostasis are important in ALS. In addition, many cellular processes have been identified as potentially contributing to disease initiation and progression, such as defects in axonal transport, autophagy, nucleocytoplasmic transport, ER stress, calcium metabolism, the unfolded protein response and mitochondrial function. Here we review the evidence from in vitro and in vivo models of C9ORF72 and TDP-43-related ALS supporting a central role in pathogenesis for endoplasmic reticulum stress, which activates an unfolded protein response (UPR), and mitochondrial dysfunction. Disruption in the finely tuned signalling between the ER and mitochondria through calcium ions may be a crucial trigger of mitochondrial deficits and initiate an apoptotic signalling cascade, thus acting as a point of convergence for multiple upstream disturbances of cellular homeostasis and constituting a potentially important therapeutic target.